Modification of Irisin Level in Overweight/Obese Women during Pregnancy and Its Association with Some Metabolic Risk Factors (Baghdad Science Journal, 2020)
Irisin is a novel myokine and adipokine, its role during pregnancy and its association with some metabolic risk factors especially pre-pregnancy body mass index (pre-BMI) need more evaluation. The aim of the study is to find whether the pre-BMI could predict irisin levels during normal pregnancy and to clarify associations of irisin with some pathological parameters.Irisin levels were estimated by ELISA in sera of 59 normal pregnant women who enrolled from December 2016 to May 2017 at Maternity Hospital, Zakho city, Kurdistan region (Iraq). Thirty-two normal-weight pregnant (pre-BMI≤24.9 kg/m2, Age=24.03 mean±3.7standard deviation) and 27 overweight/obese-pregnant (pre-BMI>25 kg/m2, Age=27.6 mean±3.9 standard deviation) were accounted for each trimester as10: 8 in first trimester, 10:10 in second trimester and12:9 in third trimester respectively. Twenty-two healthy married non-pregnant women of reproductive age served as controls, accounted as 10 normal-weight women (BMI ≤24.9 kg/m2) and 12 overweight/obese women (BMI>25 kg/m2).In pregnant women as a whole, irisin level significantly increased compared to control (p=0.003), and correlated with the pre-BMI, FBS, TP and HOMA2-IR. Pre-BMI and TP predicted irisin levels in a whole study population (p=0.011 and 0.014 respectively). In Overweight/Obese-pregnant, irisin increased significantly by 55.3% in first trimester compared with Overweight/Obese women control, then decreased progressively toward the end of gestation, correlated with TP, Albumin, FBS, HOMA2-IR and negatively correlated with gestational weight gained. TP and FBS independently predicted irisin level in Overweight/Obese-pregnant group.Conclusion: Circulating irisin levels are influenced by pre-BMI, and both of TP and FBS predict irisin levels in overweight/obese pregnant. Irisin level should be a radical factor in future studies for pathological conditions linked to hypoproteinemias such as edema and hepatic disease.